Model Konsep Teori Adaptasi Callista Roy pada Asuhan Keperawatan dengan Anorexia Nervosa - Anisah Pamungkas; Irna Nursanti (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the application of Callista Roy’s Adaptation Model in providing nursing care for a patient with anorexia nervosa. The method used was a case study involving patient Nn. S, with a comprehensive assessment based on Roy’s four adaptation modes: physiological, self-concept, role function, and interdependence. The results show that anorexia nervosa significantly affects nutritional status, physiological functions, body image, social interactions, and the ability to perform roles. The patient demonstrated maladaptive coping mechanisms related to social pressure regarding body shape and distorted self-perception. Nursing interventions based on Roy’s model were found to improve physiological balance, enhance body image, strengthen family support, and promote positive coping mechanisms. In conclusion, the application of Roy’s Adaptation Model is effective as a holistic framework that integrates biological and psychosocial aspects of nursing care for patients with anorexia nervosa, thus supporting a more comprehensive recovery process.   Keywords: Adaptation Model Roy, Anorexia Nervosa, Body Image, Coping Mechanisms, Nursing Concepts